A Packet Loss Tolerant Rendezvous Algorithm for Wireless Networked Robot Systems. Issue 4 (24th February 2017) - Manfredi, Sabato; Natalizio, Enrico; Pascariello, Claudio; Zema, Nicola Roberto
Abstract: This paper studies the coordination problem for a wireless networked robot (WNR) system. The objective is to drive the robots to keep a desired formation through local exchange of information. Nevertheless, packet losses may occur during communications among robots, thus preventing the system to reach its specific target. Specifically, the effects of an unreliable channel on the WNR performance are analyzed by considering the simulation of a corrective consensus algorithm into a network simulator. The use of a packet‐loss‐tolerant protocol is suggested to cope with heavy communication disruption. Network Simulator (NS‐3) simulation results validate the effectiveness of the proposed approach.